Magnetic Resonance Imaging and Clinical Features of Chlorfenapyr-Induced Toxic Leukoencephalopathy: A Case Report - Jong Hyuk Kim (대한영상의학회지, 2020)
Chlorfenapyr is widely used as an insecticide, despite it being fatal to humans. However, chlorfenapyr- induced central nervous system toxicity has rarely been reported. We report the magnetic resonance imaging (MRI) findings in a rare case of chlorfenapyr-induced toxic leukoencephalopathy. A 71-year-old man who had ingested chlorfenapyr approximately two weeks prior visited our hospital and presented with bilateral lower motor weakness and voiding dysfunction that had developed two days before admission. Brain MRI revealed extensive bilateral white matter abnormalities involving the corpus callosum, internal capsule, brain stem, and bilateral middle cerebellar peduncle. Furthermore, spine MRI revealed diffuse swelling and hyperintensity on the T2-weighted images.